2021
DOI: 10.1111/apce.12348
|View full text |Cite
|
Sign up to set email alerts
|

Do risk and competition trigger conditional cooperation? Evidence from public good experiments

Abstract: We investigate the effect of intra‐group competition and risk marginal per capita returns on subjects' cooperative behavior in a one‐shot public good game—following the well‐known approach proposed by Fischbacher, Gächter, and Fehr (2001) and extending the Colasante et al. (2018, 2019) parametrization. We study the interaction between environment and social preferences and test the existence of a causal relationship of risk and competition over cooperative behavior when an individual's benefit of the public go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…See also,Kuwabara (2005).10 We thank the anonymous referee for this insightful comment.11 It is relevant to point out that they use a priming methodology similar to ours (word-arrangement task) to implement a prime based on "markets and trade" with several competitive-seeming statements like, "The deal was successful." Just like our experiment, participants were tasked with re-organizing a series of sentences with five words and a subject needed to create a grammatically correct sentence after dropping one of the five words.12 Although not directly related to the volunteer's dilemma, other experimental studies with competitive-type settings attached to the provision of public goods often find a positive effect of competition on prosocial behavior-"competition fosters contributions" (see, e.g.,Andreoni, 1995;Colasante et al, 2018Colasante et al, , 2019Bergantino et al, 2021). This is also consistent with earlier studies that found greater cooperation in experimental games in developing societies with greater market integration(Henrich et al, 2001).13 Shariff et al (2016, p. 28) argue that with such priming techniques, "the relevant stimuli are supraliminally perceived but not explicitly recognized.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…See also,Kuwabara (2005).10 We thank the anonymous referee for this insightful comment.11 It is relevant to point out that they use a priming methodology similar to ours (word-arrangement task) to implement a prime based on "markets and trade" with several competitive-seeming statements like, "The deal was successful." Just like our experiment, participants were tasked with re-organizing a series of sentences with five words and a subject needed to create a grammatically correct sentence after dropping one of the five words.12 Although not directly related to the volunteer's dilemma, other experimental studies with competitive-type settings attached to the provision of public goods often find a positive effect of competition on prosocial behavior-"competition fosters contributions" (see, e.g.,Andreoni, 1995;Colasante et al, 2018Colasante et al, , 2019Bergantino et al, 2021). This is also consistent with earlier studies that found greater cooperation in experimental games in developing societies with greater market integration(Henrich et al, 2001).13 Shariff et al (2016, p. 28) argue that with such priming techniques, "the relevant stimuli are supraliminally perceived but not explicitly recognized.…”
supporting
confidence: 69%
“… Although not directly related to the volunteer's dilemma, other experimental studies with competitive‐type settings attached to the provision of public goods often find a positive effect of competition on prosocial behavior—“competition fosters contributions” (see, e.g., Andreoni, 1995; Colasante et al., 2018, 2019; Bergantino et al., 2021). This is also consistent with earlier studies that found greater cooperation in experimental games in developing societies with greater market integration (Henrich et al., 2001).…”
mentioning
confidence: 99%
“…Recently there has been an increasing interest in examining how exposure to competitive interactions impacts individuals' risky cooperation. A body of literature at the interface of psychology and behavioral economics has consistently reported that individuals embedded in a competitive setting showed higher levels of cooperation as reflected by their increased contribution to a public good [18][19][20][21][22][23] or a more homogenous distribution of resources between them and opponents (compared to a random distribution) 24 . However, in the context of simultaneous decision-making in competitive and cooperative games, existing literature has revealed that individuals' behavior in cooperative games was not affected by their participation in competitive games 25,26 .…”
Section: And Jean-claude Drehermentioning
confidence: 99%
“…It has been shown that people's contribution to public goods are influenced by the contribution of others. For example, individuals can match past and current contribution of others, increasing their own contributions, the so called 'conditional cooperation' (Fischbacher et al (2001)); or they can increase contributions because they see other individuals as competitors, which is usually called 'competitive motivation' (Bornstein et al (2002) and Bergantino et al (2021)). Moreover, individuals might increase public good provision if leaders in their communities do so, the 'follow the leader' effect (Jack and Recalde (2015) and Beekman et al (2014)).…”
Section: Literature Reviewmentioning
confidence: 99%